2006
DOI: 10.1038/nature05385
|View full text |Cite
|
Sign up to set email alerts
|

Robustness–epistasis link shapes the fitness landscape of a randomly drifting protein

Abstract: The distribution of fitness effects of protein mutations is still unknown. Of particular interest is whether accumulating deleterious mutations interact, and how the resulting epistatic effects shape the protein's fitness landscape. Here we apply a model system in which bacterial fitness correlates with the enzymatic activity of TEM-1 beta-lactamase (antibiotic degradation). Subjecting TEM-1 to random mutational drift and purifying selection (to purge deleterious mutations) produced changes in its fitness land… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
433
3
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 405 publications
(474 citation statements)
references
References 21 publications
27
433
3
1
Order By: Relevance
“…Experiments showed that many natural globular proteins are robust to mutations [40,53,55,202,360]. The observation that proteins with diverse primary sequences can be grouped into families with very similar structure and function gives further illustration of this robustness [361].…”
Section: Mutational Robustness Sequence-space Topology and Populatiomentioning
confidence: 99%
See 1 more Smart Citation
“…Experiments showed that many natural globular proteins are robust to mutations [40,53,55,202,360]. The observation that proteins with diverse primary sequences can be grouped into families with very similar structure and function gives further illustration of this robustness [361].…”
Section: Mutational Robustness Sequence-space Topology and Populatiomentioning
confidence: 99%
“…To implement the mutation, the structure is computationally modified; energy is then recalculated and compared against the pre-mutation wild-type value. DDG prediction is widely used to screen large numbers of mutations, often in combination with laboratory experiments [53][54][55][56][57]. The approach has also served as fitness estimators in simulation studies of protein evolution [58,59].…”
Section: Biophysical Consequences Of Protein Mutations 21 Mutationamentioning
confidence: 99%
“…A fraction L of all mutations are lethal, and a genome dies if it receives one or more lethal mutations. Thus, (1b) In this manifestation of survival, the surviving fraction of the population is the Poisson fraction that escapes lethal mutations (Shafikhani et al, 1997;Bershtein et al, 2006;Bloom et al, 2007). Log-linear survival across changes in U ̅ requires that L be constant.…”
Section: The Surviving Fractionmentioning
confidence: 99%
“…The data on protein survival typically violate strict log-linearity with U ̅ , at least for low mutation rates Bloom et al, 2005Bloom et al, , 2007Bershtein et al, 2006). A further distinction between the survival functions used here and some of those applied to protein survival is that the functions here are based on rates or the average number of mutations per genome/gene.…”
Section: The Surviving Fractionmentioning
confidence: 99%
See 1 more Smart Citation